Spectroscopic Characterization and Biological Effects of 1-Oxo-bisabolone-rich Pulicaria burchardii Hutch. subsp. burchardii Essential Oil Against Viruses, Bacteria, and Spore Germination - Giusy Castagliuolo; Federica Dell’Annunziata; Sara Pio; Michela Di Napoli; Alessia Troiano; Dario Antonini; Natale Badalamenti; Maurizio Bruno; Vincenzo Ilardi; Veronica Folliero; Mario Varcamonti; Gianluigi Franci; et al. (Plants)
Pulicaria species are used as herbal medicine and in the preparation of decoctions in several Asian and African regions. Among them, the plant Pulicaria burchardii is known for its medicinal properties, but comprehensive studies on its biological activity are still limited. This study examined the properties of the essential oil (EO) extracted by P. burchiardii and collected in Morocco during the flowering period. The focus was on its antimicrobial, anti-germinative, antioxidant, and antiviral activities, with the aim of evaluating its potential use in food preservation and beyond. The EO was subjected to various analyses to determine its chemical composition and biological efficacy. Specifically, GCMS and NMR analyses revealed that the EO is rich in oxygenated sesquiterpenes (72.59%), with 1-oxo-bisabolone being the predominant component (65.09%). The antimicrobial activity was tested against various Gram-positive and Gram-negative bacteria, demonstrating a significant inhibition of bacterial growth, particularly against Bacillus subtilis (MIC value of 0.6 mg/mL). The anti-germinative property was evaluated on spores of B. subtilis and other bacilli, such as Bacillus cereus, revealing a notable ability to prevent germination. For antiviral activity, the EO was tested against several pathogenic viruses including SARS-CoV-2 and HSV-1, showing an effective broad-spectrum reduction in viral replication in vitro. This study demonstrated that P. burchardii essential oil had excellent antibacterial and antiviral capabilities. The future challenge will focus mainly on the principal compound, 1-oxo-bisabolone, to demonstrate its real effectiveness as an antibacterial and/or antiviral.